Thermoplastic resin composition and molded article formed therefrom

By using a specific proportion of polyaryl etherketone and polyaryl ethersulfone resin in the thermoplastic resin composition and adding carbon nanotubes, the shortcomings of the existing composition in hardness, impact resistance and compatibility are solved, and a molded product with good balance characteristics and processing direction independence is achieved.

CN119855871APending Publication Date: 2025-04-18LOTTE CHEM CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380058102.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-16
Filing Date
2023-08-01
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing polyaryl ether ketone and polyaryl ether sulfone resin compositions have shortcomings in terms of hardness, impact resistance and balance therebetween, and have limited compatibility, resulting in performance deterioration and processing direction-dependent changes in characteristics.

Method used

A thermoplastic resin composition of about 60% to 90% by weight of polyaryl ether ketone resin and about 10% to 40% by weight of polyaryl ether sulfone resin is used, and about 0.5% to 10 parts by weight of carbon nanotubes are added to improve the hardness, impact resistance and compatibility of the composition.

Benefits of technology

A thermoplastic resin composition with good characteristics in terms of hardness, impact resistance and balance between them is achieved, ensuring good compatibility between polyaryl etherketone and polyaryl ethersulfone resin, and reducing characteristic variations according to the sample processing direction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005262822130000021
    Figure BDA0005262822130000021
  • Figure BDA0005262822130000022
    Figure BDA0005262822130000022
  • Figure BDA0005262822130000031
    Figure BDA0005262822130000031
Patent Text Reader

Abstract

The thermoplastic resin composition of the present invention comprises: about 100 parts by weight of a thermoplastic resin comprising about 60 to about 90 weight percent of a polyaryletherketone resin and about 10 to about 40 weight percent of a polyarylethersulfone resin; and about 0.5 to about 10 parts by weight of carbon nanotubes, in which the average size of the domains (polyarylethersulfone resin) in the matrix (polyaryletherketone resin) is about 0.5 [mu] m or less as measured at 10,000 and 50,000 magnifications using a scanning electron microscope (SEM). The thermoplastic resin composition is excellent in terms of hardness, impact resistance, balance of physical properties, and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermoplastic resin composition and a molded article formed therefrom, and more particularly to a polyaryletherketone / polyarylethersulfone-based thermoplastic resin composition having good properties in terms of hardness, impact resistance and balance therebetween, and a molded article formed therefrom. Background Art

[0002] Polyaryletherketone (PAEK) resins, such as polyetheretherketone (PEEK) resins, offer excellent heat resistance, chemical resistance, hardness, and fatigue resistance, making them suitable for a variety of applications including office automation, automotive, etc. However, the low impact strength of polyaryletherketone resins limits their use in applications requiring high impact resistance.

[0003] Blending with polyarylethersulfone (PAES) resin has been used to enhance the impact strength of polyaryletherketone (PAEK) resin. However, the limited compatibility between PAEK resin and PAES resin leads to the degradation of properties (such as hardness and impact strength) and significant variation of properties (hardness, impact strength, etc.) according to the processing direction (machine direction (MD) and transverse direction (TD)) of the sample, which limits their application.

[0004] Therefore, there is a need for a thermoplastic resin composition having excellent characteristics in hardness, impact resistance and a balance therebetween without deteriorating the compatibility between polyaryletherketone and polyarylethersulfone resins.

[0005] The background art of the present invention is disclosed in Korean Patent Registration No. 10-2163638. Summary of the invention

[0006]

Technical issues

[0007] An object of the present invention is to provide a thermoplastic resin composition having good characteristics in terms of hardness, impact resistance and balance therebetween.

[0008] Another object of the present invention is to provide a molded article formed from the above thermoplastic composition.

[0009] The above and other objects of the present invention will become apparent from the following detailed description of the embodiments.

[0010]

Technical solution

[0011] 1. One aspect of the present invention relates to a thermoplastic resin composition. The thermoplastic resin composition comprises: about 100 parts by weight of a thermoplastic resin, which comprises about 60 wt% to about 90 wt% of a polyaryletherketone resin and about 10 wt% to about 40 wt% of a polyarylethersulfone resin; and about 0.5 parts by weight to about 10 parts by weight of carbon nanotubes, wherein the average size of the domains (polyarylethersulfone resin) in the matrix (polyaryletherketone resin) is about 0.5 μm or less as measured by scanning electron microscopy (SEM) at magnifications of 10,000× and 50,000×.

[0012] 2. In embodiment 1, the polyaryletherketone resin may include a repeating unit represented by Formula 1.

[0013] [Formula 1]

[0014]

[0015] 3. In embodiment 1 or 2, the viscosity is measured using a capillary viscometer at a temperature of 400°C and a time of 1,000 seconds according to ASTM D3835. -1 The polyaryletherketone resin may have a melt viscosity of about 300 Pa·s to about 500 Pa·s, measured at a shear rate of .

[0016] 4. In embodiments 1 to 3, the polyarylethersulfone resin may include a repeating unit represented by Formula 2.

[0017] [Formula 2]

[0018]

[0019] 5. In embodiments 1 to 4, the viscometer was used according to ASTM D3835 at a temperature of 400°C and a time of 1,000 seconds. -1 The polyarylethersulfone resin may have a melt viscosity of about 200 Pa·s to about 400 Pa·s, as measured at a shear rate of .

[0020] 6. In embodiments 1 to 5, the melt viscosity ratio of the polyaryletherketone resin to the polyarylethersulfone resin may be in the range of about 1:1 to about 4:1.

[0021] 7. In embodiments 1 to 6, the carbon nanotubes may have an average diameter of about 3 nm to about 15 nm and an average length of about 10 μm to about 25 μm.

[0022] 8. In embodiments 1 to 7, the thermoplastic resin composition may have a glass transition temperature of about 150° C. to about 170° C. and may exhibit a single glass transition temperature.

[0023] 9. In embodiments 1 to 8, the thermoplastic resin composition may have a yield point tensile strength of about 93 MPa to 100 MPa and a tensile modulus of about 3.3 GPa to about 4.0 GPa, measured in the longitudinal direction (MD) or transverse direction (TD) of the sample at a crosshead speed of 50 mm / min on a 3.2 mm thick injection molded sample according to ASTM D638.

[0024] 10. In embodiments 1 to 9, the difference in yield tensile strength in the longitudinal and transverse directions of the injection molded sample may be about 2 MPa or less, and the difference in tensile modulus in the longitudinal and transverse directions of the injection molded sample may be about 0.2 GPa or less.

[0025] 11. In embodiments 1 to 10, the thermoplastic resin composition may have a flexural strength of about 140 MPa to about 150 MPa and a flexural modulus of about 3.2 GPa to about 4.0 GPa, measured on a 3.2 mm thick injection molded sample at a crosshead speed of 2.8 mm / min in the longitudinal direction (MD) or transverse direction (TD) of the sample according to ASTM D790.

[0026] 12. In embodiments 1 to 11, the difference in bending strength in the longitudinal and transverse directions of the injection molded sample may be about 2 MPa or less, and the difference in bending modulus in the longitudinal and transverse directions of the injection molded sample may be about 0.2 GPa or less.

[0027] 13. In embodiments 1 to 12, the thermoplastic resin composition may not show fracture in an impact strength test according to ASTM D256, where unnotched Izod impact strength is measured on a 3.2 mm thick injection molded sample in the machine direction (MD) or transverse direction (TD) of the sample.

[0028] 14. Another aspect of the present invention relates to a molded article. The molded article is formed from the thermoplastic resin composition according to any one of embodiments 1 to 13.

[0029]

Beneficial Effects

[0030] Embodiments of the present invention provide a thermoplastic resin composition having good characteristics in terms of hardness, impact resistance, and a balance therebetween, and a molded article formed therefrom. DETAILED DESCRIPTION

[0031] Hereinafter, embodiments of the present invention will be described in detail.

[0032] The thermoplastic resin composition according to the present invention includes: (A) a polyaryletherketone resin; (B) a polyarylethersulfone resin; and (C) carbon nanotubes.

[0033] (A) Polyaryletherketone resin

[0034] The polyaryletherketone resin according to one embodiment of the present invention is used together with a polyarylethersulfone resin and carbon nanotubes at a specific content ratio to improve the properties of a thermoplastic resin composition such as hardness, impact resistance, and a balance therebetween without reducing the compatibility between the polyaryletherketone resin and the polyarylethersulfone resin. The polyaryletherketone resin may include a polyaryletherketone resin used in a typical thermoplastic resin composition.

[0035] In some embodiments, the polyaryletherketone resin may include a polyaryletherketone resin including a repeating unit represented by Formula 1 (eg, a polyetheretherketone resin).

[0036] [Formula 1]

[0037]

[0038] In some embodiments, the rheometer is used according to ASTM D3835 at a temperature of 400° C. and 1,000 seconds. -1 The polyaryletherketone resin may have a melt viscosity of about 300 Pa·s to about 500 Pa·s, for example, about 310 Pa·s to about 490 Pa·s, measured at a shear rate of . Within this range, the thermoplastic resin composition may have good properties in terms of hardness, impact resistance, and a balance therebetween while ensuring good compatibility between the polyaryletherketone resin and the polyarylethersulfone resin.

[0039] In some embodiments, the polyaryletherketone resin may be present in an amount of 60 wt% to about 90 wt%, for example, about 60 wt% to about 85 wt%, based on the total weight of the thermoplastic resin including the polyaryletherketone resin and the polyarylethersulfone resin. If the content of the polyaryletherketone resin is less than about 60 wt% based on the total weight of the thermoplastic resin, the thermoplastic resin composition may have poor properties in terms of compatibility, hardness, and impact resistance between the polyaryletherketone resin and the polyarylethersulfone resin, and may exhibit significant changes in properties (hardness, impact resistance, etc.) according to the processing direction (longitudinal (MD) and transverse (TD)) of the sample. If the content of the polyaryletherketone resin exceeds about 90 wt% based on the total weight of the thermoplastic resin, the thermoplastic resin composition may have poor properties in terms of compatibility, hardness, and impact resistance between the polyaryletherketone resin and the polyarylethersulfone resin, and may exhibit significant changes in properties (hardness, impact resistance, etc.) according to the processing direction (longitudinal (MD) and transverse (TD)) of the sample.

[0040] (B) Polyarylethersulfone resin

[0041] The polyarylethersulfone resin according to one embodiment of the present invention is used together with a polyaryletherketone resin and carbon nanotubes at a specific content ratio to improve the properties of a thermoplastic resin composition such as hardness, impact resistance, and a balance therebetween without reducing the compatibility between the polyaryletherketone resin and the polyarylethersulfone resin. The polyarylethersulfone resin may include a polyarylethersulfone resin used in a typical thermoplastic resin composition.

[0042] In some embodiments, the polyaryl ether sulfone resin may include a polyaryl ether sulfone resin including a repeating unit represented by Formula 2 (eg, a polyphenylene sulfone resin).

[0043] [Formula 2]

[0044]

[0045] In some embodiments, the rheometer is used according to ASTM D3835 at a temperature of 400° C. and 1,000 seconds. -1 The polyarylethersulfone resin may have a melt viscosity of about 200 Pa·s to about 400 Pa·s, for example, about 210 Pa·s to about 390 Pa·s, measured at a shear rate of . Within this range, the thermoplastic resin composition may have good properties in terms of hardness, impact resistance, and a balance therebetween while ensuring good compatibility between the polyaryletherketone resin and the polyarylethersulfone resin.

[0046] In some embodiments, the melt viscosity ratio of the polyaryletherketone resin to the polyarylethersulfone resin may be in the range of about 1: 1 to about 4: 1, for example, about 1.05: 1 to about 2.5: 1. Within this range, good compatibility between the polyaryletherketone resin and the polyarylethersulfone resin may be ensured, whereby the domain (polyarylethersulfone resin) in the matrix (polyaryletherketone resin) may have an average size of 0.5 μm or less, the thermoplastic resin composition may exhibit a single glass transition temperature, may have good properties in terms of hardness, impact resistance, etc., and may exhibit minimal changes in physical properties (hardness, impact resistance, etc.) according to the processing directions (machine direction (MD) and transverse direction (TD)) of the sample.

[0047] In some embodiments, the polyarylethersulfone resin may be present in an amount of 10 wt% to about 40 wt%, for example, about 15 wt% to about 40 wt%, based on the total weight of the thermoplastic resin including the polyaryletherketone resin and the polyarylethersulfone resin. If the content of the polyarylethersulfone resin is less than about 10 wt% based on the total weight of the thermoplastic resin, the thermoplastic resin composition may have poor properties in terms of compatibility, hardness, and impact resistance between the polyaryletherketone resin and the polyarylethersulfone resin, and may exhibit significant changes in properties (hardness, impact resistance, etc.) according to the processing direction (longitudinal direction (MD) and transverse direction (TD)) of the sample. If the content of the polyarylethersulfone resin exceeds about 40 wt% based on the total weight of the thermoplastic resin, the thermoplastic resin composition may have poor properties in terms of compatibility, hardness, and impact resistance between the polyaryletherketone resin and the polyarylethersulfone resin, and may exhibit significant changes in properties (hardness, impact resistance, etc.) according to the processing direction (longitudinal direction (MD) and transverse direction (TD)) of the sample.

[0048] (C) Carbon nanotubes

[0049] The carbon nanotubes according to one embodiment of the present invention are used together with the polyaryletherketone resin and the polyarylethersulfone resin at a specific content ratio to improve the properties of the thermoplastic resin composition (such as hardness, impact resistance and balance therebetween) without reducing the compatibility between the polyaryletherketone resin and the polyarylethersulfone resin. For example, the carbon nanotubes may include single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes, bundled carbon nanotubes, etc.

[0050] In some embodiments, the carbon nanotubes may have an average diameter of about 3 nm to about 15 nm, for example, about 5 nm to about 13 nm, as measured by a transmission electron microscope (TEM), and may have an average length of about 10 μm to about 25 μm, for example, about 12 μm to about 20 μm, as measured by a scanning electron microscope (SEM). Within these ranges, the thermoplastic resin composition may have good properties in terms of compatibility between the polyaryletherketone resin and the polyarylethersulfone resin, and may exhibit minimal changes in properties (hardness, impact resistance, etc.) according to the processing directions (longitudinal direction (MD) and transverse direction (TD)) of the sample.

[0051] In some embodiments, the carbon nanotubes may be present in an amount of about 0.5 to about 10 parts by weight, for example, about 1 to about 9 parts by weight, relative to about 100 parts by weight of the thermoplastic resin. If the content of the carbon nanotubes is less than about 0.5 parts by weight relative to about 100 parts by weight of the thermoplastic resin, the thermoplastic resin composition may have poor properties in terms of compatibility, hardness, and impact resistance between the polyaryletherketone resin and the polyarylethersulfone resin, and may exhibit significant changes in properties (hardness, impact resistance, etc.) according to the processing direction (longitudinal (MD) and transverse (TD)) of the sample. If the content of the carbon nanotubes exceeds about 10 parts by weight relative to about 100 parts by weight of the thermoplastic resin, the thermoplastic resin composition may have poor properties in terms of fluidity and plasticity, which may lead to molding failure.

[0052] The thermoplastic resin composition according to one embodiment of the present invention may further include additives used in typical thermoplastic resin compositions. The additives may include, for example, flame retardants, fillers, antioxidants, anti-dripping agents, lubricants, mold release agents, nucleating agents, thermal stabilizers, UV stabilizers, pigments, dyes, and mixtures thereof. Relative to about 100 parts by weight of the thermoplastic resin, the additive may optionally be present in an amount of about 0.001 parts by weight to about 40 parts by weight, for example, about 0.1 parts by weight to about 20 parts by weight.

[0053] In the thermoplastic resin composition according to the present invention, the domains (polyarylethersulfone resin) in the matrix (polyaryletherketone resin) may have an average size of 0.5 μm or less (including the case where no domains are visible) as measured by a scanning electron microscope (SEM) at magnifications of 10,000× and 50,000×. If the average size of the domains exceeds about 0.5 μm, the thermoplastic resin composition may have poor properties in terms of compatibility between the polyaryletherketone resin and the polyarylethersulfone resin, hardness, and impact resistance, and may show significant changes in properties (hardness, impact resistance, etc.) according to the machine directions (machine direction (MD) and transverse direction (TD)) of the sample.

[0054] In some embodiments, the thermoplastic resin composition may have a glass transition temperature of about 150°C to about 170°C, for example, about 150°C to about 165°C, and may exhibit a single glass transition temperature. Within this range, the thermoplastic resin composition may have good properties in terms of hardness, impact resistance, etc. without reducing the compatibility between the polyaryletherketone resin and the polyarylethersulfone resin, and may exhibit minimal changes in properties (hardness, impact resistance, etc.) according to the processing direction (longitudinal direction (MD) and transverse direction (TD)) of the sample. Here, "single glass transition temperature" means that only one peak is observed in the relationship diagram of tan δ obtained by measuring the modulus of the sample of the thermoplastic resin composition using a dynamic mechanical analyzer (model name: Q800, manufacturer: TA Instruments) under the conditions of a strain of 2.5%, a frequency of 1 Hz, and a heating rate of 5°C / min.

[0055] The thermoplastic resin composition according to one embodiment of the present invention can be prepared in the form of pellets by mixing the above components and then melt-extruding at a temperature of about 350 to about 450° C. (eg, about 380 to about 420° C.) in a typical twin-screw extruder.

[0056] In some embodiments, the thermoplastic resin composition may have a tensile strength at yield point of about 93 MPa to about 100 MPa, e.g., about 95 MPa to about 99 MPa, and a tensile modulus of about 3.3 GPa to about 4.0 GPa, e.g., about 3.4 GPa to about 3.9 GPa, measured in the machine direction (MD) of the sample at a crosshead speed of 50 mm / min on a 3.2 mm thick injection molded sample according to ASTM D638.

[0057] In some embodiments, the thermoplastic resin composition may have a tensile strength at yield point of about 93 MPa to about 100 MPa, e.g., about 95 MPa to about 99 MPa, and a tensile modulus of about 3.3 GPa to about 4.0 GPa, e.g., about 3.4 GPa to about 3.9 GPa, measured in the transverse direction (TD) of the sample at a crosshead speed of 50 mm / min on a 3.2 mm thick injection molded sample according to ASTM D638.

[0058] In some embodiments, the difference in yield point tensile strength in MD and TD of an injection molded sample of the thermoplastic resin composition may be about 2 MPa or less, and the difference in tensile modulus in MD and TD of an injection molded sample of the thermoplastic resin composition may be about 0.2 GPa or less.

[0059] In some embodiments, the thermoplastic resin composition may have a flexural strength of about 140 MPa to about 150 MPa, e.g., about 141 MPa to about 149 MPa, and a flexural modulus of about 3.2 GPa to about 4.0 GPa, e.g., about 3.3 GPa to about 3.8 GPa, measured in the machine direction (MD) of the sample at a crosshead speed of 2.8 mm / min on a 3.2 mm thick injection molded sample according to ASTM D790.

[0060] In some embodiments, the thermoplastic resin composition may have a flexural strength of about 140 MPa to about 150 MPa, e.g., about 141 MPa to about 149 MPa, and a flexural modulus of about 3.2 GPa to about 4.0 GPa, e.g., about 3.3 GPa to about 3.8 GPa, measured in the transverse direction (TD) of the sample at a crosshead speed of 2.8 mm / min on a 3.2 mm thick injection molded sample according to ASTM D790.

[0061] In some embodiments, the difference in flexural strength in MD and TD of an injection molded sample of the thermoplastic resin composition may be about 2 MPa or less, and the difference in flexural modulus in MD and TD of an injection molded sample of the thermoplastic resin composition may be about 0.2 GPa or less.

[0062] In some embodiments, the thermoplastic resin composition may not show fracture in an impact strength test according to ASTM D256, in which unnotched Izod impact strength is measured on a 3.2 mm thick injection molded sample in the machine direction (MD) of the sample.

[0063] In some embodiments, the thermoplastic resin composition may not show fracture in an impact strength test according to ASTM D256, in which unnotched Izod impact strength is measured on a 3.2 mm thick injection molded sample in the transverse direction (TD) of the sample.

[0064] The molded product according to the present invention is formed by the above-mentioned thermoplastic resin composition. The thermoplastic resin composition can be prepared in the form of pellets. The prepared pellets can be manufactured into various molded products (articles) by various molding methods (such as injection molding, extrusion, vacuum molding, casting, etc.). These molding methods are well known to those of ordinary skill in the art to which the present invention belongs. The molded product has good properties in terms of hardness, impact resistance and the balance between them without reducing the compatibility between the polyaryletherketone resin and the polyarylethersulfone resin. Moreover, the molded product shows the minimum change in performance (hardness, impact resistance, etc.) according to the processing direction (longitudinal direction (MD) and transverse direction (TD)) of the sample. These characteristics make the molded product suitable for a wide range of applications, including mechanical components (such as gears, connectors, motors and bearings) and components for semiconductor / liquid crystal manufacturing equipment.

[0065] [Implementation Methods of the Invention]

[0066] Next, the present invention will be described in more detail with reference to some examples. However, it should be noted that these examples are provided for illustration only and are not to be construed as limiting the present invention in any way.

[0067] Example

[0068] The details of the components used in Examples and Comparative Examples are as follows:

[0069] (A) Polyaryletherketone resin

[0070] (A1) Polyetheretherketone resin (melt viscosity: 470 Pa·s, product name: 650G, manufacturer: Victrex Plc) was used.

[0071] (A2) Polyetheretherketone resin (melt viscosity: 350 Pa·s, product name: 450G, manufacturer: Victrex Plc) was used.

[0072] (A3) Polyetheretherketone resin (melt viscosity: 150 Pa·s, product name: KT880, manufacturer: Solvay SA) was used.

[0073] (A4) Polyetheretherketone resin (melt viscosity: 90 Pa·s, product name: 90G, manufacturer: Victrex Plc) was used.

[0074] (B) Polyarylethersulfone resin

[0075] (B1) polyphenylsulfone resin (melt viscosity: 230 Pa·s, product name: Ultrason P2010, manufacturer: BASF SE) was used.

[0076] (B2) Polyphenylsulfone resin (melt viscosity: 320 Pa·s, product name: Ultrason P3010, manufacturer: BASF SE) was used.

[0077] (B3) Polyphenylsulfone resin (melt viscosity: 360 Pa·s, product name: Radel 5100, manufacturer: Solvay SA) was used.

[0078] (C) Carbon nanotubes

[0079] Carbon nanotubes (product name: Lucan BT1003M, manufacturer: LG Chem) were used.

[0080] Examples 1 to 9 and Comparative Examples 1 to 7

[0081] The above components were mixed in the amounts listed in Tables 1, 2, 3 and 4, and then melt-extruded at 400°C to prepare a thermoplastic resin composition in the form of pellets. Here, a twin-screw extruder (L / D: 40, Φ: 45 mm) was used for extrusion. The prepared pellets were dried at 100°C for 4 hours or more, and then injection molded using a 6-ounce extruder (molding temperature: 400°C, mold temperature: 150°C) to prepare a sample. The following properties of the prepared samples were evaluated. The results are shown in Tables 1, 2, 3 and 4.

[0082] Characteristic evaluation

[0083] (1) Average domain size (unit: μm): After coating the sample with platinum, the size of each domain (polyarylethersulfone resin) in the matrix (polyaryletherketone resin) was measured at magnifications of 10,000× and 50,000× using a data input tool of a scanning electron microscope (SEM, model name: S-4800, manufacturer: Hitachi High-Technologies Corporation), and the obtained values ​​were averaged.

[0084] (2) Glass transition temperature (unit: °C): After measuring the modulus of the sample using a dynamic mechanical analyzer (model name: Q800, manufacturer: TA Instruments) under the conditions of 2.5% strain, 1 Hz frequency and 5 C / min heating rate, the temperature corresponding to the peak in the relationship graph of tan δ and temperature was determined as the glass transition temperature of the sample.

[0085] (3) Tensile strength at yield point (unit: MPa) and tensile modulus (unit: GPa): The tensile strength at yield point and the tensile modulus were measured on 3.2 mm thick injection molded specimens (size: 150 mm × 150 mm × 3.2 mm) at a crosshead speed of 50 mm / min in the machine direction (MD) and transverse direction (TD) of the specimen according to ASTM D638.

[0086] (4) Flexural strength (unit: MPa) and flexural modulus (unit: GPa): Flexural strength and flexural modulus were measured on 3.2 mm thick injection molded specimens at a crosshead speed of 2.8 mm / min in the machine direction (MD) and transverse direction (TD) of the specimens according to ASTM D790.

[0087] (5) Unnotched Izod impact strength (unit: kgf·cm / cm): Unnotched Izod impact strength was measured on 3.2 mm thick injection molded specimens in the machine direction (MD) and transverse direction (TD) of the specimen according to ASTM D256. (NB: no break)

[0088] Table 1

[0089]

[0090]

[0091] * Parts by weight: Parts by weight relative to 100 parts by weight of thermoplastic resin (A+B)

[0092] Table 2

[0093]

[0094]

[0095] * Parts by weight: Parts by weight relative to 100 parts by weight of thermoplastic resin (A+B)

[0096] Table 3

[0097]

[0098]

[0099] * Parts by weight: Parts by weight relative to 100 parts by weight of thermoplastic resin (A+B)

[0100] Table 4

[0101]

[0102]

[0103] * Parts by weight: Parts by weight relative to 100 parts by weight of thermoplastic resin (A+B)

[0104] From the above results, it can be seen that the thermoplastic resin composition according to the present invention is excellent in compatibility between the polyaryletherketone resin and the polyarylethersulfone resin, the average size of the domain (polyarylethersulfone resin) in the matrix (polyaryletherketone resin) is 0.5 μm or less, and has good characteristics in hardness (tensile strength, tensile modulus, flexural strength and flexural modulus) and impact resistance (unnotched Izod impact strength), and exhibits uniform characteristics in different processing directions (machine direction (MD) and transverse direction (TD)) of the sample.

[0105] On the contrary, the thermoplastic resin composition of Comparative Example 1, in which the content of the polyaryletherketone resin is less than the range according to the present invention and the content of the polyarylethersulfone resin exceeds the range according to the present invention, has poor characteristics in terms of hardness, impact resistance, and compatibility between the polyaryletherketone resin and the polyarylethersulfone resin, and exhibits significant changes in the characteristics (strength, impact resistance, etc.) according to the machine directions (MD and TD) of the sample; and the thermoplastic resin composition of Comparative Example 2, in which the content of the polyaryletherketone resin exceeds the range according to the present invention and the content of the polyarylethersulfone resin is less than the range according to the present invention, has poor characteristics in terms of hardness, impact resistance, and compatibility between the polyaryletherketone resin and the polyarylethersulfone resin, and exhibits significant changes in the characteristics (strength, impact resistance, etc.) according to the machine directions (MD and TD) of the sample. In addition, the thermoplastic resin composition of Comparative Example 3 in which the content of carbon nanotubes is less than the range according to the present invention has poor properties in terms of hardness, impact resistance, and compatibility between polyaryletherketone resin and polyarylethersulfone resin, and exhibits significant changes in properties (strength, impact resistance, etc.) according to the processing direction (MD and TD) of the sample; and the thermoplastic resin composition of Comparative Example 3 in which the content of carbon nanotubes exceeds the range according to the present invention has very poor properties in terms of fluidity and plasticity, resulting in molding failure and making it impossible to prepare samples for property evaluation. In addition, the thermoplastic resin compositions of Comparative Examples 5 to 7 in which the average size of the domain (polyarylethersulfone resin) in the matrix (polyaryletherketone resin) exceeds 0.5 μm have poor properties in terms of hardness, impact resistance, and compatibility between polyaryletherketone resin and polyarylethersulfone resin, and exhibit significant changes in properties (strength, impact resistance, etc.) according to the processing direction (MD and TD) of the sample.

[0106] Although some embodiments have been described herein, it will be appreciated by those skilled in the art that various modifications, variations and changes may be made without departing from the spirit and scope of the present invention. Therefore, it should be understood that these embodiments are provided only for illustration and are not to be construed as limiting the present invention in any way. The scope of the present invention should be limited by the appended claims rather than by the foregoing description, and the claims and their equivalents are intended to cover such modifications, etc. that fall within the scope of the present invention.

Claims

1. A thermoplastic resin composition comprising: About 100 parts by weight of a thermoplastic resin, including about 60 wt % to about 90 wt % of a polyaryletherketone resin and about 10 wt % to about 40 wt % of a polyarylethersulfone resin; and About 0.5 to 10 parts by weight of carbon nanotubes, Wherein the average size of the domains (the polyarylethersulfone resin) in the matrix (the polyaryletherketone resin) is about 0.5 μm or less as measured by scanning electron microscopy (SEM) at magnifications of 10,000× and 50,000×.

2. The thermoplastic resin composition according to claim 1, wherein the polyaryletherketone resin comprises a repeating unit represented by Formula 1: [Formula 1] 3. The thermoplastic resin composition according to claim 1 or 2, wherein the viscosity is measured using a capillary viscometer at a temperature of 400°C and a flow rate of 1,000 seconds according to ASTM D3835. -1 The polyaryletherketone resin has a melt viscosity of about 300 Pa·s to about 500 Pa·s when measured at a shear rate of .

4. The thermoplastic resin composition according to any one of claims 1 to 3, wherein the polyarylethersulfone resin comprises a repeating unit represented by Formula 2: [Formula 2] 5. The thermoplastic resin composition according to any one of claims 1 to 4, wherein the viscosity is measured using a capillary viscometer at a temperature of 400°C and a flow rate of 1,000 seconds according to ASTM D3835. -1 The polyarylethersulfone resin has a melt viscosity of about 200 Pa·s to about 400 Pa·s when measured at a shear rate of . 6 . The thermoplastic resin composition according to claim 1 , wherein a melt viscosity ratio of the polyaryletherketone resin to the polyarylethersulfone resin is in a range of about 1:1 to about 4:

1. 7 . The thermoplastic resin composition according to claim 1 , wherein the carbon nanotubes have an average diameter of about 3 nm to about 15 nm and an average length of about 10 μm to about 25 μm.

8. The thermoplastic resin composition according to any one of claims 1 to 7, wherein the thermoplastic resin composition has a glass transition temperature of about 150°C to about 170°C and exhibits a single glass transition temperature.

9. The thermoplastic resin composition according to any one of claims 1 to 8, wherein the thermoplastic resin composition has a tensile strength at yield point of about 93 MPa to about 100 MPa and a tensile modulus of about 3.3 GPa to about 4.0 GPa as measured on a 3.2 mm thick injection molded sample at a crosshead speed of 50 mm / min in the machine direction (MD) or the transverse direction (TD) of the sample according to ASTM D638.

10. The thermoplastic resin composition according to any one of claims 1 to 9, wherein the difference in yield tensile strength in the longitudinal and transverse directions of an injection molded sample may be about 2 MPa or less, and the difference in tensile modulus in the longitudinal and transverse directions of the injection molded sample may be about 0.2 GPa or less.

11. The thermoplastic resin composition according to any one of claims 1 to 10, wherein the thermoplastic resin composition may have a flexural strength of about 140 MPa to about 150 MPa and a flexural modulus of about 3.2 GPa to about 4.0 GPa as measured on a 3.2 mm thick injection molded sample at a crosshead speed of 2.8 mm / min in the machine direction (MD) or the transverse direction (TD) of the sample according to ASTM D790.

12. The thermoplastic resin composition according to any one of claims 1 to 11, wherein the difference in flexural strength in the longitudinal and transverse directions of an injection molded sample may be about 2 MPa or less, and the difference in flexural modulus in the longitudinal and transverse directions of the injection molded sample may be about 0.2 GPa or less.

13. The thermoplastic resin composition according to any one of claims 1 to 12, wherein in an impact strength test according to ASTM D256, the unnotched Izod impact strength is measured on a 3.2 mm thick injection molded sample in the machine direction (MD) or the transverse direction (TD) of the sample, and the thermoplastic resin composition does not show fracture.

14. A molded article formed from the thermoplastic resin composition according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Paek / paes compositions

    KR102163638B1